2018
DOI: 10.1088/1361-648x/aac40b
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb interaction rules timescales in potassium ion channel tunneling

Abstract: Assuming the selectivity filter of KcsA potassium ion channel may exhibit quantum coherence, we extend a previous model by Vaziri and Plenio (2010 New J. Phys. 12 085001) to take into account Coulomb repulsion between potassium ions. We show that typical ion transit timescales are determined by this interaction, which imposes optimal input/output parameter ranges. Also, as observed in other examples of quantum tunneling in biological systems, the addition of moderate noise helps coherent ion transport.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…Assuming a quantum perspective, we will extend our previous two-particle model, wherein we focused on the Coulomb repulsion between ions in their conduction through the SF. We showed that Coulomb strength dominates the process timescale [25]. This assumption agrees with the recent findings that there is no water involved in the potassium ion permeation.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…Assuming a quantum perspective, we will extend our previous two-particle model, wherein we focused on the Coulomb repulsion between ions in their conduction through the SF. We showed that Coulomb strength dominates the process timescale [25]. This assumption agrees with the recent findings that there is no water involved in the potassium ion permeation.…”
Section: Introductionsupporting
confidence: 91%
“…Then time is τ = t c ef f , the rates are Γs = Γ s /c ef f and Γd = Γ d /c ef f . The energy scale is c and U = U/ c is in the range [10 3 − 10 5 ] [25]. We verified that as in the twoparticle system [25], the rates Γs = Γd = 1 also minimizes the Coulomb repulsion for a system with multiple particles.…”
Section: Numerical Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…An important aspect of this which has gained more attention in recent years is the quantum behavior of ions in the channels of the biological membrane. This aspect aims to reveal the mechanism of the channels' selectivity filter [14][15][16][17] and to investigate the role of the voltage-gated channels when they are closed by applying the quantum tunneling phenomenon on ions [18][19][20].…”
Section: Introductionmentioning
confidence: 99%